2022
DOI: 10.1063/5.0083068
|View full text |Cite
|
Sign up to set email alerts
|

Which triatomic monohalosilylenes, monohalogermylenes, and monohalostannylenes (HMX) fluoresce or phosphoresce and why? An ab initio investigation

Abstract: The possibilities of emission from the A ~ 1 A and a ~ 3 A excited states of the triatomic halosilylenes, halogermylenes, and halostannylenes (HMX, M=Si, Ge, Sn, X = F, Cl, Br and I) have been explored in a series of extensive ab initio calculations. The triplet states are found to have deep bonding wells supporting an extensive manifold of vibrational levels which could give rise to observable triplet-singlet phosphorescence. The a ~ -X ~ band systems of the halosilylenes are calculated to occur at the red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…Compared to the experimental results, 21,22 the deviation is less than 0.014 Å, 1.71 and 6.61 cm À1 for the bond lengths, the bond angle and the vibrational frequencies, respectively, for the X 1 A 0 state, and 0.07 Å, 1.31 and 9.05 cm À1 for the A 1 A 00 state. There are no experimental studies on the triplet state a 3 A 00 , and our calculations are in good agreement with previous icMRCI + Q studies by Tarroni et al 27 It is worth mentioning that the A 1 A 00 and a 3 A 00 states exhibit larger bond angles (4201) compared to the X 1 A 0 state due to the promotion of an electron from a silicon-based nonbonding s orbital to an unoccupied out-ofplane Si 3p orbital. 23 Neither experimental nor theoretical studies have been performed so far on the spin-orbit-coupled states of HSiBr.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Compared to the experimental results, 21,22 the deviation is less than 0.014 Å, 1.71 and 6.61 cm À1 for the bond lengths, the bond angle and the vibrational frequencies, respectively, for the X 1 A 0 state, and 0.07 Å, 1.31 and 9.05 cm À1 for the A 1 A 00 state. There are no experimental studies on the triplet state a 3 A 00 , and our calculations are in good agreement with previous icMRCI + Q studies by Tarroni et al 27 It is worth mentioning that the A 1 A 00 and a 3 A 00 states exhibit larger bond angles (4201) compared to the X 1 A 0 state due to the promotion of an electron from a silicon-based nonbonding s orbital to an unoccupied out-ofplane Si 3p orbital. 23 Neither experimental nor theoretical studies have been performed so far on the spin-orbit-coupled states of HSiBr.…”
Section: Resultssupporting
confidence: 91%
“…There are no experimental studies on the triplet state a 3 A′′, and our calculations are in good agreement with previous icMRCI + Q studies by Tarroni et al . 27 It is worth mentioning that the A 1 A′′ and a 3 A′′ states exhibit larger bond angles (>20°) compared to the X 1 A′ state due to the promotion of an electron from a silicon-based nonbonding σ orbital to an unoccupied out-of-plane Si 3p orbital. 23…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A similar but not as extreme performance is also shown in DSiF for the CcCR + QZ ν 1 D–Si stretch at 1219.8 cm –1 , which differs from the experiment by 45.5 cm –1 or 3.9%. However, previous theoretical studies with multireference methods , agree with the present coupled cluster QFFs, as shown in Table . Additionally, the CcCR rotational constants for the state of both HSiF and DSiF are well-behaved with errors of 0.50% or less, most notably with an absolute difference of 31.2 MHz for the C 0 constant of DSiF.…”
Section: Resultssupporting
confidence: 88%